Does a better adherence to dietary guidelines reduce mortality risk and environmental impact in the Dutch sub-cohort of the European Prospective Investigation into Cancer and Nutrition?. Issue 1 (3rd August 2017) - Biesbroek, Sander; Verschuren, W. M. Monique; Boer, Jolanda M. A.; van de Kamp, Mirjam E.; van der Schouw, Yvonne T.; Geelen, Anouk; Looman, Moniek; Temme, Elisabeth H. M.
Abstract: Guidelines for a healthy diet aim to decrease the risk of chronic diseases. It is unclear as to what extent a healthy diet is also an environmentally friendly diet. In the Dutch sub-cohort of the European Prospective Investigation into Cancer and Nutrition, the diet was assessed with a 178-item FFQ of 40 011 participants aged 20–70 years between 1993 and 1997. The WHO's Healthy Diet Indicator (HDI), the Dietary Approaches to Stop Hypertension (DASH) score and the Dutch Healthy Diet index 2015 (DHD15-index) were investigated in relation to greenhouse gas (GHG) emissions, land use and all-cause mortality risk. GHG emissions were associated with HDI scores (−3·7 % persd increase (95 % CI −3·4, −4·0) for men and −1·9 % (95 % CI −0·4, −3·4) for women), with DASH scores in women only (1·1 % persd increase, 95 % CI 0·9, 1·3) and with DHD15-index scores (−2·5 % persd increase (95 % CI −2·2, −2·8) for men and −2·0 % (95 % CI −1·9, −2·2) for women). For all indices, higher scores were associated with less land use (ranging from −1·3 to −3·1 %). Mortality risk decreased with increasing scores for all indices. Persd increase of the indices, hazard ratios for mortality ranged from 0·88 (95 % CI 0·82, 0·95) to 0·96 (95 % CI 0·92, 0·99). Our results showed that adhering to the WHO and Dutch dietary guidelines will lower the risk of all-cause mortality and moderately lower the environmental impact. The DASH diet was associated with lower mortality and land use, but because of high dairy product consumption in the Netherlands it was also associated with higher GHG emissions.